The Effect of Single Leg Romanian Deadlift on the Risk of Hamstring Strain Injuries in Track and Field Athletes: A Cohort Study - Ryo Otani; Hideo Nishikawa; Shigeaki Matsunaga; Yosuke Hiroshige; Masatoshi Nakamura (International Journal of Sports Physical Therapy)
# Background and Purpose